Analysis of Pressure Distribution of Brassiere’s Under Wires (Journal of Fiber Bioengineering and Informatics, 2018)
To find out the distribution of pressure on brassiere
Keywords: Under wire; brassiere; pressure; distribution; comfort; under breast curve